1995
DOI: 10.1021/ac00110a023
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chromium Species in Environmental Samples Using High-Pressure Liquid Chromatography Direct Injection Nebulization and Inductively Coupled Plasma Mass Spectrometry

Abstract: A sensitive technique for speciation and quantification of Cr(III), Cr(VI), and total chromium has been developed using high-pressure liquid chromatography (HPLC) combined with direct injection nebulization (DIN) and inductively coupled plasma mass spectrometry (ICP-MS). A characterization and optimization of a microcolumn specifically designed for chromium speciation has been conducted. The direct injection nebulizer (DIN) was optimized to produce the best possible sensitivity for the system. Parameters affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Similarly, Bendahl et al [72] analyzed bromine-containing preservatives by UPLC-ICPMS at 50 µL min -1 , reporting detection limits comparable with those previously obtained by conventional HPLC-ICPMS. The detection limits can be further improved by increasing injection volumes [32,41], although this leads to degradation in the chromatographic separation.…”
Section: Sensitivity and Limits Of Detectionmentioning
confidence: 99%
“…Similarly, Bendahl et al [72] analyzed bromine-containing preservatives by UPLC-ICPMS at 50 µL min -1 , reporting detection limits comparable with those previously obtained by conventional HPLC-ICPMS. The detection limits can be further improved by increasing injection volumes [32,41], although this leads to degradation in the chromatographic separation.…”
Section: Sensitivity and Limits Of Detectionmentioning
confidence: 99%
“…130 The direct injection nebuliser (DIN) has so far the most popularity according to the publications on microscale trace element speciation. 119,[122][123][124][125]131,132 Absolute detection limits are reported to be one order of magnitude better when compared to those of conventional nebulisers. This improvement in absolute detection limits can be explained by the complete nebulisation of the sample into the plasma, and so no loss of analyte occurs.…”
Section: Microbore Columns For Liquid Chromatographymentioning
confidence: 99%
“…The use of a microbore anion-exchange column with a nitric acid eluent allowing the retention of Cr(VI) and elution of Cr(III) in the void volume is also described in the literature. 124,150,151 However, although good results were obtained with pure solutions, it was shown that hydrogencarbonate ions co-eluted with Cr(VI) and interfered on both 52 Cr + and 53 Cr + . Moreover, chloride ions co-eluted with Cr(III), disturbing the analysis of 53 Cr + .…”
Section: (B) Inorganic Chromium Speciation With Hplc-icp-msmentioning
confidence: 99%
“…Among them, chromium is extensively used in numerous industrial processes, such as tanning, electroplating, metallurgy or textile fabrication, which leads to the presence of this metal in waste water [2][3][4].…”
Section: Introductionmentioning
confidence: 99%